Association Between Exposure to Pesticides and ADHD or Autism Spectrum Disorder: A Systematic Review of the Literature. Issue 1 (January 2022) - Tessari, Luca; Angriman, Marco; Díaz-Román, Amparo; Zhang, Junhua; Conca, Andreas; Cortese, Samuele
Objective: To conduct a systematic review of studies assessing the relationship between exposure to pesticides and ADHD or Autism Spectrum Disorder (ASD). Methods: Based on a pre-registered protocol in PROPSERO (CRD42018107847), we searched PubMed, Ovid databases, and ISI Web of Knowledge with no date/language/document type restrictions, up to May 2019. The Newcastle Ottawa Scale was used to assess study quality. Results: Among the 29 retained studies, 13 focused on ADHD, 14 on ASD, and two on both disorders. Ten studies reported a significant association between exposure to pesticides and ADHD/ADHD symptoms and 12 studies found a significant association with ASD/ASD traits. The strengths of the association and the possible confounders controlled for varied substantially across studies. Conclusion: Whilst there is some evidence suggesting a possible link between pesticides and ADHD/ASD, heterogeneity across studies prevents firm conclusions. We provide methodological indications for future studies.